2022
DOI: 10.31219/osf.io/u7fw5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Referential Processing and Depression: A Systematic Review and Meta-Analysis

Abstract: Reward Devaluation Theory posits that depressed individuals avoid and devalue positivity, suggesting that they may be less likely to hold positive self-schemas. Previous meta-analytic reviews support this theoretical framework with regard to positivity but have not assessed for self-referential stimuli. Self-referential encoding and recall tasks assess for self-schemas and thus provide further insight into how depressed individuals process self-referential positivity. The aim of this systematic review and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Moreover, this feature demonstrated a greater influence on the model's predictions than the average valence of passages using third person pronouns as the subject. This finding is supported by previous research, which indicates that depressed individuals use fewer positive and more negative words to describe themselves than to describe others (Collins & Winer, 2022).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, this feature demonstrated a greater influence on the model's predictions than the average valence of passages using third person pronouns as the subject. This finding is supported by previous research, which indicates that depressed individuals use fewer positive and more negative words to describe themselves than to describe others (Collins & Winer, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…The role of self-schemas, in particular, has emerged as an important factor in the development and maintenance of depression (Wisco, 2009). Specifically, depressed individuals tend to describe themselves more negatively (e.g., "I am worthless") and less positively (e.g., "I am valuable") than nondepressed individuals (Collins et al, 2023;Collins & Winer, 2022). Moreover, depressed individuals tend to use more positive words to describe others (e.g., their friends) than to describe themselves (Collins & Winer, 2022).…”
Section: Role Of Self-schemasmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis found that depressed individuals endorsed more negative adjectives as self-descriptive than non-depressed individuals. Notably, this effect was moderated by depression severity, such that the endorsement of negative adjectives increases as depression severity also increases (Collins and Winer, 2022).…”
Section: Introductionmentioning
confidence: 96%